X-Ray Diffraction and Density Distribution Measurements on the Al2O3 Crystals Grown by Czochralski Method with Different Pull Rate - Hamdan Hadi Kusuma (Journal of Natural Sciences and Mathematics Research, 2015)
The Al2O3 crystal has been done by Czochralki Method with different pull rate. The effect of pull rate on the Al2O3 single crystal was characterized using X-ray diffraction and density measurement. Base on the XRD result of Al2O3 crystal, which belongs to the hexagonal system, except for the difference in the relative intensity, present diffraction data which are found to be in good agreement with those of the powder diffraction file (PDF) 43-1484 provided by the JCPDS. It was observed the structure with symmetry group D63d–R3C and has lattice constants being a = 4.759 Å, c = 12.99 Å. The density of the crystals increased with the pull rate. This phenomenon is caused by the speed of the pull rate crystal that causes changes in the heat flow in the furnace and then changed homogeneities of species distribution of atoms along the crystal. © 2015 JNSMR UIN Walisongo. All rights reserved.